INTERGENERIC HYBRIDIZATION OF GOLDFISH (Cyprinus carpio L) WITH COMET GOLDFISH (Carassius auratus) - Suparman Suparman; Hamdan Alawi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This studywas conducted from May-August 2017 at the Laboratory of Hatchery and Fish Breeding, Marine and Fisheries Faculty University of Riau, Pekanbaru. The objective of this research was to evaluate the intergeneric hybridization between Common carp (Cyprinus carpio L) and Comet goldfish (Carassius auratus). Percentage of Fertilization, hatching, growth, survival in seven days (SR-7), survival rate in thirty days (SR-30),heterosis value, and to know the morphometric and meristic characteristics of hybridized seeds. The method was an experimental method with a Completely Randomized Design (CRD), one factor three times repetition. Spawning is induced breeding using ovaprim hormone with a dose of 0.5 ml/kg. The cross was done by fertilizing the Common carp eggs with Comet goldfish sperm and otherwise the comet fishgold egg is fertilized with Common carp sperm. The results showed thathybridization was successfully. Heterosis of hybrid results positive to SR-7 parameter while the other parameters are negative. The hybrid ♀Cg × ♂Cc results have an advantage to FR, HR and SR values while the ♀Cc × ♂Cg hybrid results excel to absolute weight and length growth parameters.In general, hybrid seeds tend towards the common carp at a ratio of body width, head width, and head length to total length, while towards comet goldfish the character of height to total length compared. Keywords: intergeneric hybridization, growth, morphometric, common carp, comet goldfish